The Bactericidal Effect of CO2 Laser on Pseudomonas aeruginosa Isolated from Wound and Burn Infections, In-Vitro (Baghdad Science Journal, 2015)
A total of 60 cotton swabs are collected from patients suffering from burn wound and surgical site infections admitted to Baghdad Teaching Hospital and Burn Specialist Hospital in Baghdad city during 9/2013 to 11/2013. All cotton swabs are cultured initially on blood agar and MacConkey agar and subjected for standard bacteriological procedures for bacteriological diagnosis. Twenty samples out of sixty are identified as Pseudomonas aeruginosa by conventional methods. The results of antibiotic susceptibility test illustrate that the antibiotics resistance rate of Pseudomonas aeruginosa isolates is as follows:100% (2020) for ceftriaxone, cefepime and carbencillin, 70% (14/20) for amikacin, 65%(13/20) for tobramycin, ceftazidim and gentamycin, 55% (11/20) for ciprofloxacin and norfloxacin, 50% (10/20) for piperacillin and impeneme, 30% (6/20) for aztreonam. All Pseudomonas aeruginosa isolates are investigated for detection of some virulence factors (haemolysin, protease, lipase enzymes, and extracellular pigments) and biofilm formation. The results of virulence factors reveal that all the isolates are haemolysin, protease, lipase enzymes and extracellular pigments producer, while 95% of the isolates are biofilm producer. Six isolates are selected to irradiation by using CO2 laser according to the results of antibiotic susceptibility and virulence factors at power densities (2000, 2500, and 3000) W/cm2 with exposure time (60 and 90) second. The results of CO2 laser irradiation illustrate that CO2 laser irradiation lead to a reduction in the mean value of the viable number CFU/ml of Pseudomonas aeruginosa isolates with the increase of the power density and exposure time. The results of the statistical analysis by using analysis of variance (ANOVA) one way and least significant differences-LSD show that there are statistical significant differences in the mean of the viable number CFU/ml between different power densities and different exposure times. After irradiation, antibiotic susceptibility and virulence factors tests of the irradiated strains are performed. The current study concludes that CO2 laser has bactericidal effect on P. aeruginosa isolates without any effect on its antibiotics susceptibility and virulence factors.